2002
DOI: 10.1161/01.cir.0000015698.54752.6d
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Left Atrial Appendage Transcatheter Occlusion to Prevent Stroke in High-Risk Patients With Atrial Fibrillation

Abstract: Background-Thromboembolism due to atrial fibrillation (AF) is a frequent cause of stroke. More than 90% of thrombi in AF form in the left atrial appendage (LAA). Obliteration of the appendage may prevent embolic complications. Methods and Results-We evaluated the feasibility and safety of implanting a novel device for percutaneous left atrial appendage transcatheter occlusion (PLAATO). LAA occlusion using the PLAATO system was attempted in 15 patients with chronic AF at high risk for stroke, who are poor candi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
214
0
15

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 411 publications
(232 citation statements)
references
References 22 publications
(16 reference statements)
3
214
0
15
Order By: Relevance
“…However, a longer-time registry demonstrated that the use of septal occluders for LAA occlusion was associated with lower success and higher embolization rates when compared to the implantation of dedicated devices. * The first dedicated device for LAA occlusion was the PLAATO System (ev3, Plymouth, MN, no longer available), first implanted in 2001 25 . It consisted of a self-expandable nitinol cage covered with a non-thrombogenic PTFE membrane.…”
Section: Discussionmentioning
confidence: 99%
“…However, a longer-time registry demonstrated that the use of septal occluders for LAA occlusion was associated with lower success and higher embolization rates when compared to the implantation of dedicated devices. * The first dedicated device for LAA occlusion was the PLAATO System (ev3, Plymouth, MN, no longer available), first implanted in 2001 25 . It consisted of a self-expandable nitinol cage covered with a non-thrombogenic PTFE membrane.…”
Section: Discussionmentioning
confidence: 99%
“…45,46 It is widely believed that formation and embolism of left atrial appendage thrombi are responsible for the increased risk of stroke in AF patients. 4,47,48 Each year, Ϸ60 000 Americans with AF experience strokes; these strokes are often large and devastating, emphasizing the need for primary prevention.…”
Section: Future Directions: the Left Atrial Appendagementioning
confidence: 99%
“…P ercutaneous occlusion of the left atrial appendage (LAA) has been used as an alternative to oral anticoagulation in patients for whom this strategy is not safe. [1][2][3][4][5][6] It is a routinely performed procedure, including in Brazil. [7][8][9] Patent foramen ovale (PFO) is located more cranially in the septum, and it is believed that its use as an access route for LAA occlusion hinders the correct positioning of the delivery sheath.…”
Section: Descritoresmentioning
confidence: 99%